Perancangan Interior Gerai pada Pusat Perbelanjaan Sarinah di Malang dan Semarang - Kiki Kunthi Lestari; Setia Damayanti; Siti Rachima Mumpuni; Margaret Arni Bayu Murti; Listya Nindita; Ashri Prawesthi Dharmayati; Ramadhani Isna Putri (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2022)
Micro, Small, and Medium-Sized Enterprises are one of the businesses that sell domestic products that are of comparable quality to foreign products. The establishment of the Sarinah shopping centre as a venue for the sale of micro, small, and medium-sized enterprise products such as souvenirs, apparel, and accessories are evidence of this. To supporter Sarinah's efforts, it is vital to have retail locations with aesthetically pleasing and practical interiors. This study discusses the notion of interior space for MSME retail locations in Sarinah Malang and Sarinah Semarang as examples. Combining classroom learning with the application of social media as part of public education, particularly regarding the history of Sarinah and the design of space in MSME outlets in a Nusantara-style, was the strategy utilised to create the design. Concepts, designs, colour schemes, and materials; themes, interior styles, floor plans, sectional views, details, and viewpoints are the outcomes of this design process.